Future emerging technologies in the wind power sector: A European perspective. (October 2019) - Watson, Simon; Moro, Alberto; Reis, Vera; Baniotopoulos, Charalampos; Barth, Stephan; Bartoli, Gianni; Bauer, Florian; Boelman, Elisa; Bosse, Dennis; Cherubini, Antonello; Croce, Alessandro; Fagiano, Lorenzo; et al.
Abstract: This paper represents an expert view from Europe of future emerging technologies within the wind energy sector considering their potential, challenges, applications and technology readiness and how they might evolve in the coming years. These technologies were identified as originating primarily from the academic sector, some start-up companies and a few larger industrial entities. The following areas were considered: airborne wind energy, offshore floating concepts, smart rotors, wind-induced energy harvesting devices, blade tip-mounted rotors, unconventional power transmission systems, multi-rotor turbines, alternative support structures, modular high voltage direct current generators, innovative blade manufacturing techniques, diffuser-augmented turbines and small turbine technologies. The future role of advanced multiscale modelling and data availability is also considered. This expert review has highlighted that more research will be required to realise many of these emerging technologies. However, there is a need to identify synergies between fundamental and industrial research by correctly targeting public and private funding in these emerging technology areas as industrial development may outpace more fundamental research faster than anticipated. Highlights: A set of emerging technologies in the wind power sector was identified and studied. For each technology, an analysis of the main advantages and challenges was made. Potential for scaling each technology was identified. Technology Readiness Levels and their development trends were assessed.